PENERAPAN SISTEM PAKAR BERBASIS WEB UNTUK DIAGNOSA GANGGUAN KEHAMILAN PADA WANITA - Priska Napitu; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2024)
In the discipline of computer science, artificial intelligence, commonly referred to as AI, is a subfield that tries to make machines (computers) capable of completing activities simultaneously with and in addition to those that are performed by people. Due to a lack of information regarding pregnancy illnesses in women, the symptoms that are experienced during pregnancy, as well as the significance of pregnancy and delivery services, there is a lack of understanding regarding the period during which the fetus is developing inside the womb. This has a substantial impact on the health of both the mother and the fetus, since it carries with it an increased chance of miscarriage and maternal death since the pregnancy is being maintained. With a system that diagnoses pregnancy disorders in women, it can be used for the consultation process to find out what symptoms are solutions for pregnancy. The forward chaining method can determine solutions based on symptom data. The study's goal is to create a web-based expert system to diagnose pregnancy disorders in women. symptoms that are selected by the user, and the system that has been developed is able to offer a solution to the difficulties that have been encountered.